STRONG COLOURINGS OF HYPERGRAPHS - Rajola, Sandro; Scafati Tallini, Maria (Italian Journal of Pure and Applied Mathematics, 2010)
We de¯ne a new method of colouring for a hypergraph, in particular for a graph. Such a method is as usual meant as a partition of a hypergraph, in particular of a graph. However, it is more intrinsically linked to the geometric structure of the hypergraph and therefore enables us to obtain stronger results than in the classical case. For instance, we prove theorems concerning 3-colourings, 4-colourings and 5-colourings, while we have no analogous results in the classical case. Moreover, we prove that there are no semi-hamiltonian regular simple graphs of positive degree admitting a hamiltonian 1-colouring. Finally, we characterize the above graphs admitting a hamiltonian 2-colouring and a hamiltonian 3-colouring.